Reply to the Comments on: Concurrent Aerobic Plus Resistance Exercise Versus Aerobic Exercise Alone to Improve Health Outcomes in Paediatric Obesity: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (BMJ Publishing Group, 2019)
[No abstract available]